2020
DOI: 10.4067/s0718-58392020000300370
|View full text |Cite
|
Sign up to set email alerts
|

Understanding drought responses of sugarcane cultivars controlled under low water potential conditions

Abstract: Drought resistance mechanisms of sugarcane (Saccharum officinarum L.) vary with different conditions and locations. Understanding physiological and morphological responses of sugarcane cultivars grown under uniform and controllable conditions needs to be established. Therefore, the objective of this study was to investigate the mechanisms of drought responses of sugarcane cultivars grown under low water potential conditions via polyethylene glycol (PEG) induction. The hydroponic experiment was conducted under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Conversely, genotypes showing earlier symptoms are considered sensitive to drought [ 7 , 21 ]. The increase in photosynthetic attributes, leaf relative water content, and green leaf area in drought-tolerant genotypes relative to drought-sensitive genotypes has been observed in sugarcane [ 14 , 32 , 33 ], switchgrass [ 34 , 35 ], wheat [ 36 , 37 ], and rice [ 38 , 39 ]. Tolerance mechanisms are favorable under mild and moderate drought conditions because they allow plants to endure stress, maintain essential functions, and sustain growth during stress [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, genotypes showing earlier symptoms are considered sensitive to drought [ 7 , 21 ]. The increase in photosynthetic attributes, leaf relative water content, and green leaf area in drought-tolerant genotypes relative to drought-sensitive genotypes has been observed in sugarcane [ 14 , 32 , 33 ], switchgrass [ 34 , 35 ], wheat [ 36 , 37 ], and rice [ 38 , 39 ]. Tolerance mechanisms are favorable under mild and moderate drought conditions because they allow plants to endure stress, maintain essential functions, and sustain growth during stress [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our research, it was determined that the G3664 and G3840, which were found to have high drought tolerance, were less affected by water shortage compared to the sensitive G3837 and G3759, in terms of many characteristics. In addition, Chapae et al (2020) reported that PEG-6000 can be used to form artificial drought stress to observe the response of seedlings to water scarcity and provides an alternative tool under control conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the high stalk dry weight sugarcane cultivars under rain-fed conditions are categorized as drought-resistant cultivars [8]. Chapae et al [31] studied KK3 and UT12 under drought conditions at the early growth stage in a hydroponic system, where KK3 demonstrated good adaptation of the characteristics that promote biomass maintenance in hydroponic systems, including g s , P N , dry weight partitioning, root dry weight, and proportion of green leaves. In general, drought-resistant sugarcane cultivars conserve water in leaves by reducing water loss and maintaining water uptake in the roots [9,32,33].…”
Section: Discussionmentioning
confidence: 99%